KCC2-dependent subcellular ECl difference of ON-OFF retinal ganglion cells in larval zebrafish - Zhang, Rongwei; Zhang, Shuyi; Du, Jiu-lin (Frontiers in Neural Circuits, 2013)
Subcellular difference in the reversal potential of Cl- (ECl) has been found in many types of neurons. As local ECl largely determines the action of nearby GABAergic/glycinergic synapses, subcellular ECl difference can effectively regulate neuronal computation. The ON-OFF retinal ganglion cell (RGC) processes both ON and OFF visual signals via its ON and OFF dendrites, respectively. It is thus interesting to investigate whether the ON and OFF dendrites of single RGCs exhibit different local ECl. Here, using in vivo gramicidin-perforated patch recording in larval zebrafish ON-OFF RGCs, we examine local ECl at the ON and OFF dendrites, and soma through measuring light-evoked ON and OFF inhibitory responses, and GABA-induced response at the soma, respectively. We find there are subcellular ECl differences between the soma and dendrite, as well as between the ON and OFF dendrites of single RGCs. These somato-dendritic and inter-dendritic ECl differences are dependent on the Cl- extruder, K+/Cl- co-transporter (KCC2), because they are largely diminished by down-regulating kcc2 expression with morpholino oligonucleotides or by blocking KCC2 function with furosemide. Thus, our findings indicate that there exists KCC2-dependent ECl difference between the ON and OFF dendrites of individual ON-OFF RGCs that may differentially affect visual processing in the ON and OFF pathways.